PENERAPAN PRINSIP ANTI RIBA DALAM HUKUM SYARI’AH: Studi Komparatif antara Teks Al-Qur’an dan Praktik Ekonomi Modern - Moh Nabhan Abror; Achwan Baharuddin (EL-ADABI : Jurnal Studi Islam, 2025)
This article examines the implementation of anti-usury (riba) principles in Islamic law through a comparative study between Qur’anic texts and modern economic practices. The primary focus is to analyze how the Qur’anic prohibition of riba—supported by scholarly consensus—is realized within contemporary financial systems. This study applies a qualitative method, using thematic interpretation of riba-related verses and normative analysis, while also exploring the realities of Islamic financial institutions, fintech, and takaful insurance in Indonesia. The findings reveal that although Islamic finance is growing, its implementation faces various challenges such as the dualism of economic systems, low public literacy, product complexity, and market competition pressures. Furthermore, the emergence of anti-riba social movements plays a significant role in driving economic transformation aligned with Islamic values. The study recommends strengthening regulations, education based on maqāṣid al-sharī‘ah, and the empowerment of Islamic microfinance institutions to build a fair, inclusive, and riba-free financial ecosystem.